A rare presentation of Klippel-Trenaunay syndrome - Tanweer Karim; Upvan Singh; Navdeep S Nanda (Wolters Kluwer Medknow Publications, 2014)
The Klippel-Trenaunay syndrome (KTS) is a congenital disorder characterized by capillary malformation, varicosities and bony and soft tissue hypertrophy. This disease has several morbidities like bleeding, deep venous thrombosis, embolic complications and in some cases enlargement of limb that may require amputation. Vascular malformations are segmented and never cross midline. However, we came across a case, a 45-year-old male, who presented with varicosity of veins and deformity of left lower limb besides cavernous hemangiomas (port-wine stains) scattered all over his face, chest, back, gluteal region, groin and legs since birth. Multiple paravertebral soft tissue masses and bladder hypertrophy were also noted due to involving neurofibromatosis. Simultaneous occurrence of KTS and neurofibromatosis is rarely seen in clinical practice.